2005
DOI: 10.1177/230949900501300214
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Spontaneous Rupture of Achilles Tendons: A Case Report

Abstract: Spontaneous bilateral rupture of Achilles tendon is rare. Rupture of the Achilles tendon has been described in patients on oral corticosteroid therapy. The sudden dorsiflexion of the plantar-flexed foot is the usual mechanism of injury. Spontaneous bilateral rupture is common in the degenerated tendon, which is often seen in patients with long-term corticosteroid therapy. This case is unusual because the patient has never taken steroids. We discuss the mechanism of injury and other probable causes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 5 publications
(9 reference statements)
0
11
0
3
Order By: Relevance
“…Hayes, et al [19] presented their case and suggested that smoking may have been a causative factor. Rao, et al [21] reported another case but their patient had hypothyroidism and was taking thyroxine and they surmised that hypercholesterolemia and hypothyroidism lead to degenerate tendon which eventually ruptured. Habusta [9] reported two cases in healthy patients however both patients had long term Achilles tendonitis and were gymnasts.…”
Section: Discussionmentioning
confidence: 99%
“…Hayes, et al [19] presented their case and suggested that smoking may have been a causative factor. Rao, et al [21] reported another case but their patient had hypothyroidism and was taking thyroxine and they surmised that hypercholesterolemia and hypothyroidism lead to degenerate tendon which eventually ruptured. Habusta [9] reported two cases in healthy patients however both patients had long term Achilles tendonitis and were gymnasts.…”
Section: Discussionmentioning
confidence: 99%
“…Les premières descriptions rapportant l'association de cette rupture à une corticothérapie au long cours ont été faites dans les années 1960 [8][9][10]. Elles surviennent le plus souvent sur un tendon altéré par une maladie nécessitant le traitement cortisonique [11].…”
Section: Discussionunclassified
“…However, only a few studies have reported a link between oral GCs and the risk of Achilles tendon rupture [5,6]. Considering occasional case reports of patients receiving long-term GC treatment due to systematic diseases or autoimmune disorders, who experienced spontaneous Achilles tendon rupture [7][8][9], it is important to determine the exact mechanism by which the Achilles tendon is weakened by GC.…”
Section: Introductionmentioning
confidence: 99%